(untitled) (Revista Latino-Americana de Enfermagem, 2010)
This qualitative study focused on proxemic feelings and feelings of detachment and ambiguity among professors-nurses concerning their experiences. This study aimed to reveal the meanings of sensibility held by being-professor-nurse in teaching and learning to be and do nursing. The theoretical-philosophical support is based on Merleau-Ponty's existential phenomenological approach and the hermeneutics phenomenology of Paul Ricoeur was used. Nineteen professors-nurses from a Higher Education institution in the South of Brazil were interviewed between November and December 2006. Sensibility was revealed as the capacity to observe details in order to intervene in a situation the best way possible, and also as a way to break with exclusive models of the cognitive-instrumental rationality of science and technique, since sensibility is the basis for developing other ways of teaching and learning to be and do Nursing.